2003
DOI: 10.1021/ie030288b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grafted Lewis Base Groups on the Phase Behavior of Model Poly(dimethyl siloxanes) in CO2

Abstract: The impact of various Lewis bases on the miscibility of siloxane polymers in CO 2 was investigated using both ab initio calculations and experimental phase behavior studies. A series of sidechain functional silicones were synthesized containing various Lewis bases in the side chain, and their phase behavior was compared in CO 2 at 295 K. Calculations showed that interactions between CO 2 and ethers (either a dialkyl ether or the ether oxygen in an ester group) should be as favorable as interactions between CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 48 publications
8
140
0
Order By: Relevance
“…We have found that the MP2 level of theory gives results in fairly good agreement with coupled-cluster with single, double, and perturbative triple excitations calculations on similar systems [6]. A larger basis set, aug-cc-pVDZ, was used for single point energy calculations on the 6-31 þ G(d) optimized structures.…”
Section: Simulation Methodsmentioning
confidence: 79%
See 4 more Smart Citations
“…We have found that the MP2 level of theory gives results in fairly good agreement with coupled-cluster with single, double, and perturbative triple excitations calculations on similar systems [6]. A larger basis set, aug-cc-pVDZ, was used for single point energy calculations on the 6-31 þ G(d) optimized structures.…”
Section: Simulation Methodsmentioning
confidence: 79%
“…Propyl acetate (PA) and propyl dimethylamine (PDMA) functional siloxane copolymers were prepared according to the procedure described earlier [6].…”
Section: Synthesis Of Functional Siloxane Copolymersmentioning
confidence: 99%
See 3 more Smart Citations